Without remorse - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 1993)
A formative episode in the life of the Clancy's character John Kelly, known as "Mr Clark". In Vietnam, special operations veteran Kelly was known as "the snake" - the man whose footsteps no one ever heard. Now, in 1970, back in the USA, footsteps were all around him.